Allometric models to estimate biomass and carbon capture of the Albizia carbonaria in the Nariño coffe zone (2020)
Generation of knowledge in agroforestry systems with coffee requires a significant supply of tree species that regulate light, are friendly to biodiversity and the soil; these functions are fulfilled by Albizia carbonaria. In a coffee zone in the Nariño state, 50 plants were planted to evaluate total dry biomass (BT) and carbon capture (CC) in the species, from allometric models. During 600 days after sowing, bimonthly measurements were made in five plants of plant height (PH), basal stem diameter (BSD), normalized diameter at breast height (BH), leaves number (LN) and branches number (BN). Using the destructive method, the fresh weight of roots, stems and leaves was obtained to get the BT. Ca was taken from the product BTx0.5. In addition, the relative (RGR) and absolute growth rate (AGR) were calculated. With the exception of NHvsTRC, the correlation analysis indicated a high association between all the estimated variables. LN and BSD were adjusted to the linear model, the PH to the quadratic model, the RGR to a third-degree polynomial, with low scores in the coefficient of determination, mean square of the error, AIC and BIC. BT and Ca are explained through BSD and PH, using the Husch and Shumacher-Hall models, characterized by their low mean square error values, AIC and BIC and high coefficient of determination. The stem was the source of BT with percentages higher than 50%.